Data-informed stepped care to improve youth engagement in HIV care in Kenya: a protocol for a cluster randomised trial of a health service intervention. Issue 10 (31st October 2022) - Kohler, Pamela; Agot, Kawango; Njuguna, Irene N; Dyer, Jessica; Badia, Jacinta; Jiang, Wenwen; Beima-Sofie, Kristin; Chhun, Nok; Inwani, Irene; Shah, Seema K; Richardson, Barbra A; Chaktoura, Nahida; et al.
Abstract : Introduction: Adolescents and youth living with HIV (AYLHIV) have lower retention in care, adherence to treatment, and viral suppression compared with adults. Stepped care is a process by which clients are assigned to increasingly intensive services or 'steps' according to level of need. Differentiated care, in which stable clients access less frequent services, can be combined with stepped care to align needs and preferences of youth to promote optimal engagement in care. Methods and analysis: This hybrid type I effectiveness implementation cluster randomised trial aims to evaluate a data-informed stepped care (DiSC) intervention for AYLHIV. AYLHIV ages 10–24 receiving care at 24 HIV treatment facilities in Kisumu, Homabay and Migori counties in Kenya will be enrolled. Twelve facilities will be randomised to the DiSC intervention, and 12 will provide standard care. A clinical assignment tool developed by the study team will be used at intervention sites to assign AYLHIV to one of four steps based on risk for loss to follow-up: differentiated care, standard care, counselling services or intensive support services. The primary clinical outcome is retention in care, specifically missed visits (failure to return within 30 days for any visit) and 12-month loss to follow-up. Implementation outcomes are based on the Reach, Effectiveness, Adoption, Implementation and Maintenance framework. Proportions of missed visits will be compared using mixed effect models clustered by facility and participant. Ethics and dissemination: This study has been approved by the University of Washington Institutional Review Board (STUDY00011096), Maseno University Ethical Review Committee (MUERC/00917/20) and the Kenya National Commission for Science, Technology and Innovation (444824). AYLHIV provide written informed consent when legally permitted, or assent with caregiver permission for minors. Study staff will work with a Community Advisory Board, including youth members, to disseminate results via discussions, presentations, journal publications and local or international conferences. Trial registration number: NCT05007717 .